Voluntary wheel running access produces opposite effects in male and female rats on both palatable diet consumption and associated ventral striatal opioid- and dopamine-related gene expression - Kocum, Courtney G.; Cam, Yonca; Shay, Dusti A.; Schweizer, Tim A.; Konrad, Ella R.; Houska, Tabitha K.; Sardina, Carlos A.; Schachtman, Todd R.; Vieira-Potter, Victoria J.; Will, Matthew J. (Frontiers in Integrative Neuroscience, 2024)
The relationship between physical activity levels and feeding behaviors has been a focus of preclinical research for decades, yet this interaction has only recently been explored for potential sex differences. The aim of the present study was to isolate sex-dependent effects of voluntary wheel running (RUN) vs. sedentary locked wheel (SED) home cage conditions on palatability-driven feeding behavior using a 2-diet choice task between standard chow and a high-fat diet. The sex-dependent effects of physical activity on feeding behavior were examined following a within-subject novel reversal design of physical activity conditions (i.e., RUN > SED > RUN), to assess temporal sensitivity of the interaction. Following the final 2 weeks of reestablished and sustained RUN vs. SED conditions in separate groups of both males and females, reward-related opioid and dopamine gene expression within the nucleus accumbens (Acb) brain region were analyzed. Results demonstrated that the initial RUN > SED transition led to sex-dependent effects of SED condition, as males increased, and females decreased their high fat consumption, compared to their respective high fat consumption during previous RUN condition phase. Following reintroduction to the RUN condition, males decreased, and females increased their high fat consumption, compared to their separate SED control group. Last, sex-dependent shifts in ventral striatal opioid- and dopamine-related gene expression were observed to parallel the behavioral effects. The major findings of the study reveal that SED and RUN home cage conditions shift palatability-driven feeding in the opposite direction for males and females, these effects are sensitive to reversal, and these sex-dependent feeding behaviors track sex-dependent changes to critical reward-related gene expression patterns in the Acb. Considering the present high rates of sedentary behavior and obesity, furthering our understanding of the interaction between physical activity (or lack thereof) and feeding behavior should be a priority, especially in the context of these divergent sex-dependent outcomes.